Sexual Risk Behaviors Among Persons Diagnosed With Primary and Secondary Syphilis Who Reported High-Risk Substance Use: Data From the National Notifiable Diseases Surveillance System, 2018. Issue 2 (2nd February 2022) - Copen, Casey E.; Brookmeyer, Kathryn A.; Haderxhanaj, Laura T.; Hogben, Matthew; Torrone, Elizabeth A.
Abstract : This analysis of national syphilis surveillance data describes the prevalence of sexual risk behaviors among persons diagnosed with primary and secondary syphilis who reported high-risk substance use. Supplemental digital content is available in the text. Abstract : Background: Recent increases in high-risk substance use (HRSU; i.e., injection drug use, heroin, methamphetamine, crack/cocaine) have coincided with rising primary and secondary (P&S) syphilis rates. To further understand these trends, we examined sexual risk behaviors among women, men who have sex with women only (MSW), and men who have sex with men (MSM) who were diagnosed with P&S syphilis in 2018 and reported HRSU. Methods: Data on HRSU and sexual risk behaviors among persons with P&S syphilis were drawn from syphilis case reports in 2018 from the National Notifiable Diseases Surveillance System. Persons with P&S syphilis were asked about sexual risk behaviors in the past 12 months including exchange sex for drugs/money, sex while intoxicated and/or high on drugs, sex with a person who injects drugs (PWID), sex with an anonymous partner, and number of sex partners. We describe percentages and adjusted prevalence ratios (aPRs) for women, MSW, and MSM reporting these behaviors by age, race/Hispanic ethnicity, type of drug used, and incarceration history (both in the past 12 months). Results: Among 19, 634 persons diagnosed with P&S syphilis in 2018 with information on HRSU, 29.3% of women, 22.7% of MSW, and 12.4% of MSM reported HRSU. Among those reporting HRSU, percentages reporting exchange sex ranged from 17% to 35% (highest for women), whereas reports of anonymous sex ranged from 44% to 71% (highest for MSM). In this population, sexual risk behaviors were more commonly reported among those with a recent incarceration history than those without such history. Among those reporting injection drug use or heroin use, percentages reporting sex with a PWID ranged from 51% to 77%. In adjusted models, HRSU was significantly associated with one or more sexual risk behaviors for women (aPR, 2.63 [95% confidence interval CI, 2.39–2.90]; MSW: aPR, 1.38 [95% CI, 1.31–1.46]; and MSM: aPR, 1.30 [95% CI, 1.26–1.34]). Conclusions: Collaborative partnerships across the US public health system could help address barriers to timely clinical care among persons diagnosed with P&S syphilis who report HRSU.